Effect of pH on the Transport Capacity of Na+ Across the Isolated Omasal and Ruminal Epithelia of Sheep - Ali, Osama H. A.; Alameen, Ahmed O.; Abdoun, Khalid A.; Elkhair, Nawal M.; Martens, H. (Journal of Veterinary Medicine and Animal Production, 2021)
This study was conducted in attempt to characterize the electroneutral transport of Na+ across isolated omasmal and ruminal epithelia of sheep after treatment with pH and amiloride. The conventional Ussing chamber technique was used to measure the mucosal to serosal flux (Jms), the serosal to mucosal flux (Jsm), the net flux (Jnet), the short circuit current (Isc), and tissue conductance (Gt) of isolated epithelia. A total of 12 pairs of omasmal and ruminal epithelia were used for each treatment, which categorized as: control group (pH 7.4), low pH group (pH 6.4), amiloride group (pH 7.4) and amiloride + low pH group (pH 6.4). The unidirectional transport values of Na+ were significantly (p<0.001) higher in the omasum compared to the rumen. Lowering the pH to 6.4 significantly (p<0.001) enhanced the unidirectional transport of Na+ in the omasum accompanied by marked changes in the electrochemical parameters (Isc and Gt); however, the enhancement of the unidirectional flux of Na+ in the rumen did not reach the significant level. Application of amiloride in the mucosal side caused a significant (p<0.001) reduction in Jms, Jsm and Jnet of both epithelia. The findings confirmed that Na+ transported by means of electroneutral transport systems in the omasum was similar to the system confirmed previously in the rumen. The electroneutral transport of Na+ in the omasum is more efficient than the that in the rumen.